2018
DOI: 10.1101/362814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-autonomous regulation of astrocyte activation by the circadian clock protein BMAL1

Abstract: Circadian clock dysfunction is a common symptom of aging and neurodegenerative diseases, though its impact on brain health is poorly understood. Astrocyte activation occurs in response to diverse insults, and plays a critical role in brain health and disease. We report that the core clock protein BMAL1 regulates astrogliosis in a synergistic manner via a cell-autonomous mechanism, and via a lesser non-cell-autonomous signal from neurons. Astrocyte-specific Bmal1 deletion induces astrocyte activation in vitro a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 53 publications
4
36
0
Order By: Relevance
“…Indeed and for example, BMAL1 deletion in SCN neurons can cause partial astrocyte activation, while BMAL1 deletion in SCN astrocytes induced astrogliosis and astrocyte dysfunction (Lananna et al, 2018 ). In addition, circadian disruption can induce GFAP expression (Lananna et al, 2018 ), while aging (Wyse and Coogan, 2010 ) and inflammation (Curtis et al, 2015 ) have been shown to suppress BMAL1 levels, thus potentially influencing astrocyte activation state as well (Lananna et al, 2018 ). However, loss of BMAL1 in astrocytes does not disrupt circadian rhythm (Tso et al, 2017 ).…”
Section: Astrocytesmentioning
confidence: 99%
“…Indeed and for example, BMAL1 deletion in SCN neurons can cause partial astrocyte activation, while BMAL1 deletion in SCN astrocytes induced astrogliosis and astrocyte dysfunction (Lananna et al, 2018 ). In addition, circadian disruption can induce GFAP expression (Lananna et al, 2018 ), while aging (Wyse and Coogan, 2010 ) and inflammation (Curtis et al, 2015 ) have been shown to suppress BMAL1 levels, thus potentially influencing astrocyte activation state as well (Lananna et al, 2018 ). However, loss of BMAL1 in astrocytes does not disrupt circadian rhythm (Tso et al, 2017 ).…”
Section: Astrocytesmentioning
confidence: 99%
“…Studies determining whether Bmal1 regulates Fabp7 mRNA indirectly via Rev-erbα or whether the Fabp7 gene promoter also has functional E-box binding sites will be crucial for identifying the clock-regulated expression of this gene. Fabp7 mRNA expression was also shown to be upregulated in mice with deletion of Bmal1 in neurons and astrocytes [13]. Future studies using cell-specific knock-down of Bmal1 to determine whether disruption of core clock genes in astrocytes regulates circadian Fabp7 mRNA expression will be important for our understanding of how clock-controlled genes in non-neural cells regulate pathways affecting behavior.…”
mentioning
confidence: 97%
“…Previously, various lines of Bmal1 −/− animals showed spontaneous pathogenic changes in the CNS and/or worsened outcomes following acute neurotoxic injury or autoimmune neuroinflammation. Thus, aging-associated reactive astrogliosis, reduced expression of anti-oxidant enzymes, increased oxidative stress, neuroinflammation, and synaptic damage were observed after germ line-, pan-neural-, or astrocyte-selective deletion of Bmal1 20,57 . In addition, age-dependent chronic BBB dysfunction was associated with loss of Bmal1 from nestin + PCs 58 .…”
Section: Discussionmentioning
confidence: 99%